THE POSSIBILITY OF EDUCATIONAL DATA MINING FOR PRACTICAL SKILLS DEVELOPMENT IN LEARNING MANAGEMENT SYSTEM - Mamčenko, Jelena; Piščikienė, Inga; Šustickienė, Brigita; Šileikienė, Irma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The paper presents comprehensive study of applicability of Moodle virtual learning environment to the development of practical skills. The quantitative research involved faculty students and  lecturers of Vilnius College of Technologies and Design. Data analysis indicated that currently the most beneficial method to develop practical skills is blended method. This result, however, turned out to be more positive for students than for lecturers, the latter being less willing to employ technology alongside traditional classroom. The article also briefly describes data mining technologies that are often employed to plan study process, as well as depicts data flows and action sequence of the future survey. The study also puts forward recommendations for further research.